Gesso agrícola na produção de milho e soja em solo de alta fertilidade e baixa acidez em subsuperfície em plantio direto - Maschietto, Evandro Henrique Gonçalves (2009)
There are doubts about the conditions in which a favorable effect of the application of gypsum on the yield of grain crops can be expected. In order to evaluate the influence of gypsum application in the soil chemical attributes, in mineral nutrition of maize (Zea mays L.) and soybean (Glycine max L. Merrill) yield in no-till system, an experiment was carried out in an clay Oxisol with high organic carbon content and low acidity in Guarapuava (PR). The treatments, arranged in randomized complete block with four replications, consisted of four of gypsum: 0, 4, 8 and 12 t ha-1. Gypsum was applied in September 2005, set on the soil satesurface. The corn, hybrid Pionner 30R50, was sown in October 2005, and the transgenic soybeans, MAGIC cultivar, was sown in November 2006 and 2007. During the autumn-winter seasons of 2005 to 2007, black oats (Avena strigosa Schreb) was sown in the experimental area. Gypsum application, after 9, 18 and 30 months, increased the content of exchangeable Ca2+ and S-SO4 2- available in the soil profile (0-60 cm) and the Ca2+/Mg2+ ratio in surface layers and subsoil. The application of gypsum caused leaching of exchangeable of Mg2+ and K+ the subsoil. There was positive and significant correlation (p < 0.01) between the content of S-SO4 2- extracted with ammonium acetate and acetic acid with calcium phosphate. The rates of gypsum increased the content of S in leaf and grain yield of maize. The maximum technical efficiency (MET) for corn occurred with a rate of 7.8 t ha-1 of gypsum. Nutrition and grain yield of soybean were not affected by the application of gypsum. The different responses of corn and soybean to the application of gypsum might have been caused by the supply of P, S and the increase in exchangeable Ca2+ and of the Ca2+/Mg2+ ratio in the soil. The application of gypsum proved to be an efficient practice to maximize corn yield, even in soil of high fertility and low acidity under notill system.